Banking on circularity: can financial institutions become the engines of a regenerative economy? - Williams Chibueze Munonye; Daniella Ifunanya Munonye (Frontiers in Environmental Economics)
This paper investigates the transformative potential of financial institutions in driving the shift toward a regenerative economy, with a particular emphasis on embedding circularity within financial and economic systems. In the face of escalating ecological degradation, resource exhaustion, and systemic inequality, there is an urgent imperative to reimagine traditional economic models through restorative and sustainable frameworks. This study critically examines the role of banks, investment firms, and allied financial entities in operationalizing circular economy (CE) principles across lending practices, asset allocation, and investment portfolios. It explores key mechanisms such as green bonds, circular economy-linked loans, sustainable finance instruments, and the financing of closed-loop supply chains, assessing their capacity to enable regenerative business transitions. The paper also interrogates the influence of evolving policy regimes and regulatory frameworks in either enabling or constraining financial sector alignment with circular imperatives. Drawing from interdisciplinary literature spanning sustainable finance, ecological economics, and institutional theory, the research identifies both structural barriers and emergent opportunities shaping the financial sector's response to circularity. Findings reveal that while promising innovations exist, institutional inertia, risk perception biases, and valuation misalignments remain critical obstacles. Nevertheless, the study contends that financial institutions hold a catalytic role in accelerating systemic circular transitions if supported by coherent policy instruments, reconfigured risk models, and metrics that reflect long-term ecological value. The paper concludes that advancing a regenerative economy requires integrated approaches that converge finance, governance, and sustainability science to embed circularity at the core of capital flows and economic design.